Pengaruh Inflasi, Tingkat Suku Bunga, Dan Nilai Tukar Terhadap Harga Saham Pada Perusahaan Sub Sektor Logam Dan Sejenisnya Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016 – 2021 - Devita Eka Yuniar Wulandari; Ustadus Sholihin; Edi Murdiyanto (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to determine whether there is an influence of the variables of inflation, interest rates, and exchange rates on stock prices in metal sub-sector companies and the like listed on the Indonesia Stock Exchange for the period 2016 - 2021. The population in this study were all metal sub-sector companies and the like as many as 16 companies, then the researchers used a sampling technique using purposive sampling method. The results of this study indicate that the probability value of the inflation variable of 0.1955 is greater than the significant value of 0.05 so that inflation has no partial effect on stock prices. The interest rate variable has no significant effect partially on stock prices where the probability value of 0.2426 is greater than the significant value of 0.05. The exchange rate variable has a partially significant effect on stock prices where the probability value of 0.0247 is smaller than the significant value of 0.05. Inflation, interest rate, and exchange rate variables together have a significant effect on stock prices where the F-statistic probability value of 0.000 is smaller than the significant value of 0.05.